2011
DOI: 10.1889/1.3621091
|View full text |Cite
|
Sign up to set email alerts
|

P‐66: Wet Chemical Metallization for High‐End Flat Panel Display Manufacturing

Abstract: Recently the use of Copper as a conductor material for Thin Film Transistor (TFT) structures has received increasing attention in the Flat Panel Display industry [1,2]. Since sputtering of thick Cu layers has serious disadvantages Flat Panel Display (FPD) manufacturers are considering wet chemical Cu deposition as a viable process alternative. Depending on the required film properties like conductivity and surface roughness either electroless or electrolytical Copper deposition can be applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…[4][5][6][7][8]13,14,16,17,19,27,30,31 The silane solution was made in ethanol to facilitate penetration into small diameter holes. The silane treated surface was baked to hydrolyze the silane to improve its adhesion to the glass and to remove excess volatile material.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6][7][8]13,14,16,17,19,27,30,31 The silane solution was made in ethanol to facilitate penetration into small diameter holes. The silane treated surface was baked to hydrolyze the silane to improve its adhesion to the glass and to remove excess volatile material.…”
Section: Resultsmentioning
confidence: 99%
“…These include mechanical techniques (grit blasting, abrasive grinding) and chemical methods (etching with acidic fluoride solutions) or combinations of the two. 4,10,11 Both of these approaches can be somewhat effective, but they have limitations manifested by the inability to affect the holes and by the difficulty of handling thin glass substrates used for interposers. Another variation on the mechanical interlocking approach is roughening by application of a discontinuous photo mask on the glass followed by acid fluoride etching to produce a pattern of recessed and raised regions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cu produced by the vacuum evaporation method exhibits significant stress and poor adhesion to glass substrates or insulating layers such as SiO 2 , and SiNx. To overcome this issue, several methods have been reported that Ni films as an intermediate layer by electroless plating were deposited, and then Cu electrodes were formed on this layer [2][3][4].…”
Section: Introductionmentioning
confidence: 99%